Perbaikan Pengalaman Pengguna Pada Aplikasi Perangkat Bergerak OVO Menggunakan Metode Diary Study dan User Journey - Filza Dikaputra; Retno Indah Rokhmawati; Lutfi Fanani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The OVO application is an e-money application used in the digital. Usage of the OVO application has started since 2017 which has over a million user based on the statistics garnered from the playstore and a short survey conducted by the author, the OVO application has gathered many complaints about its features and display. Therefore, the researcher conducted an evaluation using the diary study method to gain a detailed and conceptual insight on experiences and responses in regards to the usage of the OVO application to know the user experience because there has not been a user experience evaluation towards the OVO application. The diary study method was conducted with interviews, scenario work, and documentation towards five respondents over the course of 2 weeks. During the process of analyzing the diary study data, the author utilized a user journey method to map the user's journey when interacting with the application, which was being researched therefore gaining a journey map of each user containing details such as stage, touchpoint, thinking and feeling and ideas for improvement. The problems found in this research was about the improvement of features and display. Recommendation results regarding features and display was gained by looking at the journey map of the user which were then used as a base for improvement and creation of a prototype user interface. The success rate of the overall process of this research was calculated based on validation result from interviews from respondent and expert regarding the improvement of the display of the user interface which was conducted to gain data which corresponded with the goal of this research.